Design, development and evaluation of novel lead compounds as HIV-1 enzyme inhibitors - Sekgota, Khethobole Cassius (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
This project has been concerned with the application of the Baylis-Hillman methodology to the synthesis of medicinally important diketo acid analogues (cinnamate ester-AZT conjugates and 3-hydroxy ester-AZT conjugates) as dual-action HIV-1 IN/RT inhibitors; and on exploratory studies in the preparation of 3-(amidomethyl)-(1H)-2-quinolones as PR inhibitors; and (1H)-2- quinolone-AZT conjugates as dual action IN/RT inhibitors. A series of Baylis-Hillman adducts has been prepared, typically in moderate to excellent yield, by reacting 2-nitrobenzaldehyde with methyl acrylate, ethyl acrylate and methyl vinyl ketone in the presence of 1,4- diazabicyclo[2.2.2]octane (DABCO). Subsequently, various transformations that include conjugate addition of primary and secondary amines to the Î±,ÃŸ-unsaturated moiety to obtain 2- (aminomethyl)-3-hydroxy-3-(2-nitrophenyl)propanoate derivatives, effective SN2Â´ substitution of the BH ÃŸ-hydroxy by a Vilsmeier-Haack in situ-generated chloride to afford Baylis-Hillman allyl chlorides, iron in acetic acid-catalyzed cyclisation to 3-acetoxymethyl-(1H)-2-quinolone derivatives were achieved. Thus, using the Baylis-Hillman methodology, two nuanced classes of diketo acid analogues were constructed. These involved conjugating appropriate propargylamine derivatives with AZT using the click"Ÿ reaction. In an exploratory study, the quinolone derivative, precisely 3-acetoxymethyl- (1H)-quinol-2-one, was transformed into 3-hydroxymethyl-(1H)-quinol-2-one using potassium carbonate in a mixture of methanol and water (1:1). Following successful hydrolysis, the resulting alcohol was transformed to the corresponding chloride, 3-chloromethyl-(1H)-quinol-2- one, using thionyl chloride. Subsequent nucleophilic substitution afforded 3-(aminomethyl)- (1H)-2-quinolone derivatives which were subsequently transformed to 3-(amidomethyl)-(1H)-2- quinolones; and 3-[(propargylamino)-methyl]-(1H)-quinol-2-one as precursors to quinolone- AZT derivatives. All compounds were characterized by NMR, IR, and where appropriate, high resolution MS
Keywords: Enzyme inhibitors; Viruses -- Reproduction; HIV (Viruses)